2018
DOI: 10.1007/s12094-018-1878-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic paraaortic surgical staging in locally advanced cervical cancer: a single-center experience

Abstract: Pretherapeutic laparoscopic paraaortic lymphadenectomy for locally advanced cervical carcinoma allows the adaption of radiotherapy fields to avoid false-positive and false-negative imaging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These articles were not part of the initial search result, because the title nor abstract included the 'lymphadenectomy' search term or synonyms. The final analysis included 16 studies [14,15,18,19,[25][26][27][28][29][30][31][32][33][34][35][36] reporting on 18 cohorts which were suitable for quantitative meta-analysis with pooling of upstaging outcomes.…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These articles were not part of the initial search result, because the title nor abstract included the 'lymphadenectomy' search term or synonyms. The final analysis included 16 studies [14,15,18,19,[25][26][27][28][29][30][31][32][33][34][35][36] reporting on 18 cohorts which were suitable for quantitative meta-analysis with pooling of upstaging outcomes.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Characteristics of the 18 cohorts within 16 studies included in the quantitative synthesis are outlined in Table 2. Six studies [15,25,27,29,30,35] (38%) were prospective and 10 studies [14,18,19,26,28,[31][32][33][34]36] (63%) were retrospective by design. All studies used laparoscopic procedures.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para-aortic lymph node (PALN) metastasis plays an important role in the metastasis of cervical cancer. It was reported that 13.5–20.2% of patients with locally advanced cervical cancer (LACC) had positive PALNs ( 2 5 ). For patients with FIGO stage IB, IIB and III disease, the incidences of PALN metastasis are 5%, 16% and 25% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a pathological diagnosis of para-aortic LNs, surgical biopsy with laparoscopy guidance under general anesthesia is sometimes performed [8,9]. However, imageguided percutaneous biopsy is preferred because it is less invasive, has lower complication rates, and has lower costs [2].…”
Section: Introductionmentioning
confidence: 99%